New Insights into the multifunctional mechanisms of polyaniline/Fe₃O₄-biochar in anaerobic co-digestion: Electron shuttling, microbial community succession, and metabolic regulation - Boyang Li; Sijia Chen; Jinzhi Zou; Jianwei Zhao; Jinxu Zhang; Mengjun Zeng; Yingjie Sun; Weidong Ye (Process Safety and Environmental Protection, 2026)

Comparative Analysis of Sensory Quality and Microbial Communities Between Medium–High- and High-Temperature Daqu From Shangqiu Region - Mengjun Cui; Yurong Wang; Jixiang Sun; Jun Zhang; Haibao Fan; Yanju Li; Zhuang Guo; Huijun Zhao (Current Microbiology, 2026)

Design of structurally enhanced dual-network high internal phase emulsion gels for 3D-printable plant-based fat substitutes using carboxymethyl cellulose/heat-treated soy protein isolate and k-carrageenan - Yifei Liu; Yu Xia; Yiqiang Dai; Mengjun Sun; Xiudong Xia; Mingsheng Dong (Food Chemistry, 2026)

Characterization and Assessment of Sheep-Origin Probiotic Bacillus licheniformis B63 Strain for Potential Use in Intestinal Health and Disease - Meng Hou; Yabin Lu; Mengjun Ye; Na Li; Yawei Sun; Gang Yao; Jinquan Wang; Fangfang Yin; Qimin Peng; Sheng Jia; Rui Shi; Xuxiang Wang (Probiotics and Antimicrobial Proteins, 2025)

Screening of Spinal Muscular Atrophy Carriers and Prenatal Diagnosis in Pregnant Women in Yancheng, China - Huilin Sun; Jianli Zheng; Qing’e Zhang; Feifei Ying; Yadong Fu; Yongjuan Guan; Jing Wu; Yueyun Zhou; Jingjing Dong; Mengjun Xu; Fangfang Yang; Ning An; et al. (Biochemical Genetics, 2025)

Decoding the biochemical dialogue: metabolomic insights into soybean defense strategies against diverse pathogens - Min Qiu; Mengjun Tian; Yaru Sun; Huaibo Li; Wenwen Huang; Haibing Ouyang; Shaoyan Lin; Chen Zhang; Ming Wang; Yuanchao Wang (Science China Life Sciences, 2024)

Cropland inundation mapping in a mountain dominated region based on multi-resolution remotely sensed imagery and active learning for semantic segmentation - Hao Jiang; Jianhui Xu; Xun Zhang; Xia Zhou; Yangxiaoyue Liu; Mengjun Ku; Kai Jia; Xuemei Dai; Yishan Sun; Shuisen Chen (Journal of Hydrology, 2024)

The potential benefits and mechanisms of protein nutritional intervention on bone health improvement - Yonghui Yu; Xinping Li; Mengjun Zheng; Linyue Zhou; Jingjie Zhang; Jing Wang; Baoguo Sun (Critical Reviews in Food Science and Nutrition, 2024)

Nanotechnology-based optical sensors for Baijiu quality and safety control - Wei Dong; Zhen Fan; Xiaolong Shang; Mengjun Han; Baoguo Sun; Caihong Shen; Miao Liu; Feng Lin; Xiaotao Sun; Yanfei Xiong; Bo Deng (Food Chemistry, 2024)

Biodegradable active packaging: Components, preparation, and applications in the preservation of postharvest perishable fruits and vegetables - Linyu Nian; Mengjun Wang; Xiaoyang Sun; Yan Zeng; Yao Xie; Shujie Cheng; Chongjiang Cao (Critical Reviews in Food Science and Nutrition, 2024)

Soil Enzyme Activity and Stoichiometry Change with Perennial Mugwort Cropping Cultivation Year in Central China - Zhenxing Zhou; Xuedan Li; Zhaolin Sun; Mengjun Hu; Ying Li; Kunpeng Zhang; Shijie Han (Journal of Soil Science and Plant Nutrition, 2023)

Fatty hepatocyte-derived exosomal miR-122 promotes lipid synthesis and reduces immunocompetence in grass carp (Ctenopharyngodon idella) - Ronghua Lu; Lulu Yang; Wenya Zhang; Shenzong Jia; Mengjun Lin; Jian Sun; Yuru Zhang; Guoxing Nie (Aquaculture, 2023)

Contribution of stochastic processes to the microbial community assembly on field‐collected microplastics - Yuanze Sun; Mengjun Zhang; Chongxue Duan; Na Cao; Weiqian Jia; Zelong Zhao; Changfeng Ding; Yi Huang; Jie Wang (Environmental Microbiology, 2021)
Summary A growing body of evidence suggests that microplastics may be colonized with a unique microbiome, termed ‘plastisphere’, in aquatic environments. However, the deep mechanisms (deterministic and/or stochastic processes) underlying the community assembly on microplastics are still poorly understood. Here, we took the estuary of Hangzhou Bay (Zhejiang, China) as an example and examined the assembly mechanisms of bacterial communities in water and microplastic samples. Results from high‐throughput sequencing showed that Proteobacteria, Firmicutes, and Actinobacteria were the dominant phyla across all samples. Additionally, microorganisms from plastisphere and planktonic communities exhibited contrasting taxonomic compositions, with greater within‐group variation for microplastic samples. The null model analysis indicated the plastisphere bacterial communities were dominantly driven by the stochastic process of drift (58.34%) and dispersal limitation (23.41%). The normalized stochasticity ratio (NST) also showed that the community assembly on microplastics was more stochastic (NST > 50%). Based on the Sloan neutral community model, the migration rate for plastisphere communities (0.015) was significantly lower than that for planktonic communities (0.936), potentially suggesting that it is the stochastic balance between loss and gain of bacteria (e.g., stochastic births and deaths) critically shaping the community assembly on microplastics and generating the specific niches. This study greatly enhanced our understanding of the ecological patterns of microplastic‐associated microbial communities in aquatic environments.

Transcriptome analysis reveals the effects of temperature on growth in tadpoles of spiny-bellied frog (Quasipaa boulengeri) - Wenqiao Fan; Mengjun Huang; Jingming Xu; Meixia Zhang; Yusong Jiang; Mingcheng Cai; Hanchang Sun; Xiaoying Li (Aquaculture International, 2021)

Effect of ionic liquid [MIm]HSO4 on WPCB metal-enriched scraps refined by slurry electrolysis - Yaping Qi; Xiaoxia Yi; Yugai Zhang; Fansong Meng; Jiancheng Shu; Furong Xiu; Zhi Sun; Shuhui Sun; Mengjun Chen (Environmental Science and Pollution Research, 2019)

Biological properties and genomics analysis of vB_KpnS_GH-K3, a Klebsiella phage with a putative depolymerase-like protein - Ruopeng Cai; Zijing Wang; Gang Wang; Hao Zhang; Mengjun Cheng; Zhimin Guo; Yalu Ji; Hengyu Xi; Xinwu Wang; Yibing Xue; Sadeeq ur Rahman; Changjiang Sun; et al. (Virus Genes, 2019)

Isolation and identification of a Bacillus subtilis HZ-72 exhibiting biocontrol activity against flax seedling blight - Taimeng Tan; Jiuxiang Zhu; Airong Shen; Jilie Li; Yongting Yu; Mengjun Zhang; Mengrui Zhao; Zhimin Li; Jia Chen; Chunsheng Gao; Yi Cheng; Litao Guo; et al. (European Journal of Plant Pathology, 2019)

Decolorization of textile dye RB19 using volcanic rock matrix immobilized Bacillus thuringiensis cells with surface displayed laccase - Juan Wan; Xiaowen Sun; Cheng Liu; Mengjun Tang; Lin Li; Hong Ni (World Journal of Microbiology and Biotechnology, 2017)

Physiological and antioxidant responses of Basella alba to NaCl or Na2SO4 stress - Jianfeng Ning; Shaoying Ai; Shaohai Yang; Lihua Cui; Yong Chen; Lili Sun; Ronghui Wang; Mengjun Li; Zhaobing Zeng (Acta Physiologiae Plantarum, 2015)